Fixed transport costs and international trade - Didier Laussel; Raymond Riezman (Center for Economic Studies and ifo Institute (CESifo), 2006)
We develop a simple two country model of international trade that assumes that there is a fixed cost of doing international trade. We show that this leads to multiple equilibria that can be Pareto-ranked. We examine the stability properties of these equilibria.
Keywords: F1; F11; 330